Possible Co-productions of Change Among Police Leaders and Police Officers in the Norwegian Police Reform - Cathrine Filstad; Tom Karp (Nordic Journal of Studies in Policing, 2023)
This article investigates role ambiguity, discretion and job crafting among leaders and followers in change processes. Our findings are based on a sample of 464 police officers nested in 261 police leaders among 4495 respondents. We find that high discretion enables job crafting, where job crafting directs police leaders and police officers to positively engage in change and hence to reduce role ambiguity. However, high discretion solely among police officers to ensure job crafting and the reduction of role ambiguity is not supported, and high discretion among both leaders and police officers is only partially supported. Instead, our main finding is that the leaderʼs discretion will moderate police officersʼ role ambiguity. The leaderʼs work discretion will also ensure that police officers approach job crafting through engagement and coping. Therefore, co-productions of change between the leaderʼs discretion and the followersʼ job crafting engagement will reduce role ambiguity in implementing change.